The Analysis of the Fetal Abdominal Wall and Gastrointestinal Tract Abnormalities in a Single Tertiary Center - Gokhan Bolluk; Suleyman Cemil Oglak; Merih Cetinkaya; Isil Turan Bakirci; Oyhan Demirali; Mehmet Cok; Handan Turhan Karakus; Yasin Onur; Emine Zeynep Yilmaz (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: We aimed to evaluate the fetuses with gastrointestinal anomalies and anterior abdominal wall defects detected in the prenatal period in our clinic and to analyze their perinatal outcomes.